The effect of IFRS on the financial ratios: Evidence from banking sector in the emerging economy - Ayalew Ali Abebe (Cogent Economics & Finance)
Financial ratios are ratios that are used to measure a company’s performance by analyzing its financial records. In light of this claim, this study investigates the effect of IFRS on the financial ratios among seventeen (17) Ethiopian commercial banks. The research hypotheses are addressed by comparing financial ratios computed under Ethiopian GAAP with those computed under the IFRS regime from 2016 to 2020 using Wilcoxon Signed Rank and the Normality Test. The finding revealed that IFRS has a significant effect on the liquidity ratio of commercial banks in Ethiopia, and banks reported higher liquidity under IFRS than under Ethiopian GAAP. The finding also revealed that IFRS has a significant effect on commercial banks’ return on equity and that banks recorded a higher return on equity under IFRS than under Ethiopian GAAP. Moreover, the study found IFRS has a significant effect on the leverage ratio of commercial banks in Ethiopia, and banks reported lower leverage under Ethiopian GAAP than under IFRS. However, the finding revealed that IFRS has an insignificant effect on the return on assets of commercial banks in Ethiopia, and banks recorded a lower return on assets under IFRS than under Ethiopian GAAP. The study concluded that the difference in return on equity, liquidity, and leverage of commercial banks following the adoption of IFRS is significant. Therefore, investors and financial analysts should pay close attention to the return on equity (ROE), liquidity ratio (LR), and leverage (LEV) because they are significantly affected by the adoption of IFRS.